Incredibility of perfect threats in repeated games: The dilemma of a rational player - Ernst Mohr (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1985)
The implicit assumption made when deterrence solutions to repeated games are constructed, is that perfectness is a sufficient condition for the credibility of threats. In this paper it is shown that the validity of this assumption hinges on another assumption which proves to be unsatisfactory - namely that players exhibit a different rationality at different stages of the game. A consequence of making rationality independent of time is that sufficient conditions for the credibility of threats fail to exist.
Keywords: 330